Thin film processes II - Vossen, John L.; Kern, Werner, 1925- (Thin film processes ;, 1991)
This sequel to the 1978 classic, Thin Film Processes, gives a clear, practical exposition of important thin film deposition and etching processes that have not yet been adequately reviewed. It discusses selected processes in tutorial overviews with implementation guide lines and an introduction to the literature. Though edited to stand alone, when taken together, Thin Film Processes II and its predecessor present a thorough grounding in modern thin film techniques. Key Features * Provides an all-new sequel to the 1978 classic, Thin Film Processes * Introduces new topics, and several key topics presented in the original volume are updated * Emphasizes practical applications of major thin film deposition and etching processes * Helps readers find the appropriate technology for a particular application.